Estudio de factibilidad para la creación de una empresa comunitaria de elaboración de horchata en la Parroquia Jimbilla y su comercialización en la Ciudad de Loja - SOZORANGA MEDINA, KATY PAULINA (2018)
Community development means that within a town the people who live there work and participate in agricultural, artisanal, tourist and associative marketing activities to add value to their crops and to improve their living conditions. The purpose of this work is to offer the consumer an organic product, taking advantage of the diversity of medicinal plants that exists in the rural sector. The general objective is: To determine the financial feasibility for the creation of a community company for the production of horchata in the Jimbilla parish and its commercialization in the city of Loja. The methodology used is the deductive method that gathers the general information to analyze in a particular way and the inductive method that starts from the particular to the general. Information was collected from the primary information sources through the structurally constructed surveys that are aimed at families in the city of Loja and interviews conducted with the 4 companies that produce the same product. The sources of secondary information were taken as reference the different Theses in the library of the National University of Loja, web pages on the Internet to take statistical data into account. In the Market Study, the units purchased by the 51,122 families with an average consumption of 109 units and the offer of the 4 competing companies with 3`433,200 units are compared, the Unsatisfied Demand is of 1`167,357 units per year. In the Marketing Plan the consumption of horchata in the city of Loja is high due to the medicinal benefits of the plants it contains, there are also companies dedicated to the production and marketing that currently export the product for which the local supply decreases, having an important niche in the market. 5 The Technical Study specifies that the installed capacity is 350 kilograms for 6,000 units per day and that it will work with a utilized capacity of 82.49 kilograms for 840 daily units, with an initial market share of 15%. The Financial Study determines that the company requires an investment of $ 103,000 dollars, with internal financing by three partners with a value of $ 63,000.00 dollars and external financing through a loan to Ban-Ecuador with an amount of $ 40,000 $ 00 First Year's production costs are $ 88.643,46 with first-year income of $ 122,304.00 with a Retail price of 70 cents and the Profit of the Profit and Loss statement is $ 20.085,25 dollars. The results of the present study determine the feasibility of the project, by means of financial indicators such as: the Net Present Value is of $116.900,68 for which it is feasible to make the investment; the Internal Rate of Return 31,10%, is greater than the opportunity rate, for which the project is feasible; Benefit / Cost ratio for each dollar invested will earn 50 cents; Period of Capital Recovery is in 3 years, 2 months and 8 days; the Sensitivity Analysis supports an increase in costs of 16,16 % and in the decrease of Revenues it supports 10,96%. Finally, it is concluded that the project is feasible since the results obtained in the financial evaluation are positive and allow the future implementation of the company. In addition, it is recommended to start the project to create jobs and give value to crops in rural areas,